Implementasi Kebijakan Sertifikasi Guru Dalam Rangka Meningkatkan Profesionalitas Guru di Kota Yogyakarta - KURNIAWAN, BACHTIAR DWI (Universitas Muhammadiyah Yogyakarta, 2011)
This research was conducted to determine teacher certification policies, especially the line of portofolio,in order to improve profesionalism teachers. Research certification policy implementation especiallywant to see how far the process of implementation conducted by the executive, and what factorsinfluence teacher certification policy implementation in Kota Yogyakarta. Further research is intendedto see the impact of teacher certification policy toward teacher professionalism in teaching andlearning. This research was conducted using qualitative methods with descriptive approach. Thisstudy found several things, including: first, in terms of teacher certification process of policyimplementation in both the City Department of Education and LPTKs can be said to run well andsmoothly, just have a little problem, both are experiencing problems related to the limited facilities andsupporting infrastructure. It happened because the central government did not allocate budget tosupport the implementation of the program. Second, in terms of policy impact, there has been noincrease in certified teachers' professionalism significantly. The attitude of teachers in conductingcertification policy is only visible when pursuing welfare only, while the quality of teaching receivedless attention